ENTREPRENEURIAL ORIENTATION AND COMPETITIVE ADVANTAGE AS THE ANTECEDENTS OF SMES PERFORMANCE - Muhammad Kevin Mirza Hutagalung; Wismiarsi, Tri; Muhril Ardiansyah; Dhian Kusumawardhani (Fakultas Ekonomi Universitas IBA Palembang, 2025)
Small and medium-sized enterprises (SMEs) are critical to economic growth, representing a significant portion of businesses in industrialized economies. SMEs are the backbone of Indonesia's economy, supporting approximately 50 million people. This study examines the impact of different Entrepreneurial Orientations (EO), including innovativeness, proactiveness, and risk-taking, on the financial performance of SMEs. It aims to identify which EO behaviors and dynamic capabilities are most important for SMEs' success and the role of competitive advantage in influencing performance. The study provides a comprehensive understanding of factors driving SME success by investigating the relationship between EO and performance, determining the relative impact of each EO dimension, and analyzing how competitive advantage influences performance. Targeting experienced adults, it focuses on the unique impact of EO on SME performance. The main results show that EO improves SMEs' performance and competitive advantage, significantly impacting performance. However, competitive advantage does not moderate the relationship between EO and performance; it functions as an independent variable. The study concludes that encouraging proactive behavior, innovation, and risk-taking, along with investing in competitive advantage, are critical strategies for improving SME performance. These insights offer valuable guidance for SMEs aiming to thrive in a fast-paced business environment.